Indole-3-lactic acid suppresses colorectal cancer via metabolic reprogramming - Shizhen Zhou; Kai Wang; Jiandong Huang; Zhen Xu; Qinggang Yuan; Lixiang Liu; Zhifeng Wang; Ji Miao; Hao Wang; Tingting Wang; Wenxian Guan; Chao Ding (Gut Microbes)
Research indicates that abnormal gut microbiota metabolism is linked to colorectal cancer (CRC) progression, but the role of microbiota-related tryptophan metabolism disruption remains unclear. Using metagenomic sequencing and targeted Trp metabolomics, our research identified that CRC patients had abnormal indole-3-lactic acid (ILA) levels, which were related to tumor malignancy. Exogenous ILA administration suppressed CRC development in AOM/DSS induced and xenograft mice models. Furthermore, in vitro experiments demonstrated that ILA inhibits tumor cell proliferation, migration, and anti-apoptotic capabilities. Mechanistically, ILA appears to directly occupy the phosphorylation sites of STAT3, leading to a reduction in intracellular phosphorylated STAT3 (p-STAT3) levels and the inhibition of the HK2 pathway, thereby downregulating glucose metabolism in cancer cells. Notably, this inhibition is independent of the aryl hydrocarbon receptor (AHR). In conclusion, our research findings demonstrate that alterations in tryptophan metabolism among CRC patients can influence tumor progression and reveal a novel mechanism through which ILA exerts its inhibitory effects on CRC. These findings offer new insights into the role of gut microbiota in CRC and identify potential clinical therapeutic targets.